2013
DOI: 10.1038/srep02121
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Regulated Nucleosome Dynamics

Abstract: A strong correlation between nucleosome positioning and DNA methylation patterns has been reported in literature. However, the mechanistic model accounting for the correlation remains elusive. In this study, we evaluated the effects of specific DNA methylation patterns on modulating nucleosome conformation and stability using FRET and SAXS. CpG dinucleotide repeats at 10 bp intervals were found to play different roles in nucleosome stability dependent on their methylation states and their relative nucleosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 47 publications
7
65
0
Order By: Relevance
“…In addition, the methyl groups may locally alter the major and minor grooves, which appears especially detrimental to nucleosome stability where CG major grooves face toward the histones (Jimenez-Useche et al, 2013). Either or both of these effects would disfavor nucleosomes positioned over densely methylated regions, because such nucleosomes would either be unstable or fail to form in the first place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the methyl groups may locally alter the major and minor grooves, which appears especially detrimental to nucleosome stability where CG major grooves face toward the histones (Jimenez-Useche et al, 2013). Either or both of these effects would disfavor nucleosomes positioned over densely methylated regions, because such nucleosomes would either be unstable or fail to form in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that methyltransferase activity is generally reduced by nucleosomes, which apparently results in preferential methylation of DNA outside or at the edges of nucleosome cores (Felle et al, 2011; Gowher et al, 2005; Jiang et al, 2011; Kelly et al, 2012; Okuwaki and Verreault, 2004; Robertson et al, 2004; Takeshima et al, 2006, 2008), whereas another study instead showed that genomic methylation is modestly enriched within nucleosome core DNA (Chodavarapu et al, 2010). On the other hand, several studies have suggested that methylated DNA has effects on the positioning of nucleosomes (Collings et al, 2013; Jimenez-Useche et al, 2013; Pennings et al, 2005; Pérez et al, 2012), though biological functions for such effects have not been clearly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Besides influencing gene expression, DNA methylation is involved in higherorder chromatin structure, regulating nucleosome dynamics. 27 In fact, it has been demonstrated that hypomethylation increases nuclear clustering of pericentric heterochromatin, thus directly influencing chromatin organization. 28 Furthermore, large hypomethylated blocks with extreme gene expression variability is a universal, defining epigenetic alteration in human solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…28 Furthermore, large hypomethylated blocks with extreme gene expression variability is a universal, defining epigenetic alteration in human solid tumors. 27 These blocks correspond to large organized chromatin K9 modifications and lamina-associated domains, 29,30 regions that expand during differentiation 31 and are associated with transcriptional repression. 32,33 One may hence speculate that the observed hypomethylation of noncoding regions in i(12p) reflects chromatin remodeling and nuclear positioning that may enable cellular adaptation to aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also evidence that methylation of TFBS may occur after TF release rather than cause it [24][25][26][27][28][29][30][31]. In this model, methylation is merely a byproduct of other epigenetic processes, serving as a means of crosstalk among other epigenetic factors such as nucleosomes and TFs that may act non-concurrently [21,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%